Inverse Modeling of Structural Contact Mechanics Using the Finite Element Method - Zaytseva, T. A. (Science and Transport Progress, 2025)
Surpose. The research aims to develop and solving an inverse contact problem for two elastic bodies with different stiffnesses, enabling the identification of interaction parameters including friction zones, adhesion, sliding, and separation. A variational mathematical model is formulated, A finite element model is constructed. The use of ANSYS, automated via APDL, allows for the implementation of inverse modeling, considering the complex behavior of the system under external loading. Methodology.The study is based on a step-by-step approach to constructing the inverse contact problem, considering transitions between interaction modes (adhesion, sliding, separation), mathematical formalization, and numerical modeling using finite element analysis in ANSYS. First, a direct problem is formulated; based on its analysis, an inverse problem is constructed to identify unknown interaction parameters. A finite element model is then created, followed by result analysis. Findings.An inverse contact problem for two deformed bodies with different stiffnesses is formulated, taking into account the modes of adhesion, sliding, and separation. A finite element model is created in the ANSYS. Originality. The study proposes an integrated analytical-programmatic approach to solving the inverse contact problem for bodies with varying mechanical characteristics, considering zones of adhesion, sliding, and separation. The novelty lies in the combination of a variational mathematical problem formulation with Tikhonov regularization and finite element analysis, automated through APDL scripts within the ANSYS environment. Practical value. The developed methodology for solving inverse contact problems based on the analytical approach and its implementation in the ANSYS environment proves to be an effective tool for analyzing complex mechanical systems. The algorithm allows for the identification of contact interaction parameters (friction, adhesion zones, sliding, separation) based on actual loading conditions.